Challenges for students in translating sentences among Indonesian-English and Its Solutions - Ismail, Ismail; Mustakim, Mustakim; Hasan, Hasan (Maspul Journal of English Studies, 2023)
In eastern Indonesia, students face various difficulties in learning English. Especially English translation skills are their weak point. It is important to think about how our students' problems in using English have a certain foundation. This article investigates the problems of Indonesian English learners by analyzing some of the mistakes in their English-Indonesian translations in four aspects. This paper also offers some solutions to the problem. This study follows a descriptive and analytical method. This research was applied to students at the Faculty of Education, Muhammadiyah University of Enrekang, third year students. The student subjects consisted of 23 students studying English at the English Language Education Study Program at Muhammadiyah Enrekang University. The findings of this study emphasize that Indonesian students, especially eastern Indonesia, face problems in translation. Analysis of translation errors from the semantic category is more dominant on errors involving inappropriate word choices and the use of prepositions. In the syntactic errors’ category, the dominant error is the use of tenses. Whereas in pragmatic errors, the errors that often appear are excessive literal translations or ambiguous translations and also missing words or meanings or omission words. Students have insufficient background knowledge about how to translate English into Indonesian or vice versa. Based on these findings, the researcher recommends that translation should be considered when it is taught. Students should be given many topics to translate during their academic year and lecturers should use motivating methods to improve students' skills in translation.